The Therapeutic Effects of Crocus sativus L . and Its Constituents on the Improving Treatment of Azoospermia: A Narrative Review - Faraz Khakshour; Melika Hadad Tehran; Jamal Jalili Shahri; Farid Zeynali; Fahimeh Lavi Arab (Health Science Reports, 2026)
ABSTRACT Background and Aims Azoospermia, defined as the complete absence of sperm in the ejaculate, is a major cause of male infertility and is classified into obstructive and non‐obstructive forms. While obstructive azoospermia is primarily mechanical in origin, non‐obstructive azoospermia (NOA) is characterized by impaired spermatogenesis and is frequently associated with oxidative stress, inflammation, and hormonal dysregulation. Crocus sativus L . and its bioactive constituents exhibit antioxidant and anti‐inflammatory properties that may target underlying pathophysiological mechanisms involved in NOA. This review discusses the potential adjunctive role of Crocus sativus L . in the context of NOA, with emphasis on oxidative stress–related pathways. Methods This paper is a narrative review identified through relevant literature of electronic databases, including PubMed, Scopus, Web of Science, and Google Scholar. Peer‐reviewed experimental studies written in English that examined the antioxidant and anti‐inflammatory effects of Crocus sativus L . and its bioactive compounds on male reproductive health. Results Available studies suggest that Crocus sativus L . bioactives may help attenuate oxidative stress, modulate inflammatory mediators, and support testicular structure and spermatogenesis in experimental models of chemical, radiation, and metabolic injury. Evidence indicates improvements in antioxidant enzyme activity, reductions in lipid peroxidation, and potential preservation of hormonal balance. However, clinical data are limited, and variability in dosage, extract composition, and study design precludes definitive conclusions about reproductive outcomes. Conclusion Crocus sativus L . and its bioactive compounds could have supportive effects in contexts of testicular oxidative and inflammatory stress, but their clinical relevance in NOA remains uncertain. Further well‐controlled human studies are needed to clarify their potential therapeutic role.